Perancangan Boiler untuk Proses Sterilisasi pada Baglog Jamur Tiram - Akbar, Ronald (JTM-ITI (Jurnal Teknik Mesin ITI), 2019)
The production process is the core of an industry that certainly relies on a variety of equipment to help the process run. Oyster mushroom baglog industry is one of the agricultural industries that needs to be developed in its production equipment because of its good market prospects and high economic potential with a clear market segment. But there is a problem that often faced by the baglog farmers, the problem is the sterilization process from baglog itself is not good, so the quality of the oyster mushroom will decrease or worse is the crop failure. Therefore an appropriate boiler is needed that it can increase the yield and quality of a baglog oyster mushroom industry. Boilers that are designed will follow the existing standards, which are in accordance with the ASME (American Society of Mechanical Engineers) Boiler and Pressure Vessel Code (BPVC) standards and coupled with simulations in the form of adding loads to the boiler model using Pro Engineer Wildfire 4.0 software.